Comparative evaluation of haemoglobin estimation amongst pregnant women in Ibadan: Hemocue – B Haemoglobin analyzer versus haemiglobincyanide (Standard) method as the gold standard (2008)
This was a comparative crossectional study that was conducted among 557 antenatal women at the University College Hospital, Ibadan, Nigeria between 1st April and 30th May 2006. The study compared the accuracy of haemoglobin estimation using an automated HemoCue B analyzer kit with a standard laboratory method (haemogloincyanide) as the gold standard. The result showed a positive correlation of HaemoCue haemoglobin results when compared with the standard methods (Pearson’s correlation coefficient = 0.892; p value = 0.000). We concluded that the use of the automated HemoCue kit for haemoglobin estimation gives an objective assessment which overcomes the challenge of extra skilled manpower or power outages in rural areas thereby enhancing access to quality of care in resource poor countries